The Effect of Transcultural Nursing, Child Healthcare Model and Transtheoretical Model Approaches to Knowledge and Culture of Family - Kadek Ayu Erika (Jurnal Ners, 2014)
Introduction: Urban lifestyle fueled by excessive food intake in overweight and obese children. Famili esassumethatobese children are healthy and have no health problems. Strategies to improve the knowledge and culture of the family is the approaches of TCN, CHM dan TTM. This study aims to prove the influence of TCN, CHM and TTM to knowledge and culture’s familyin controlling lifestyle of over weight and obese children.Method: This research was conducted in the areas of Biring kanaya and Tamalanrea Subdistricts, Makassar from August 2013 to March 2014. It used the Quasy Experiment design namely pre-test and post-test with control group design. Research subjects were parents of overweight or obese children in the 4th, 5th, and 6th grade of elementary school. There were 31 samples in the treatment group; and 33 samples in the control group. There were selected by using purposive sampling technique. The intervention was given for six months by providing guide books on healthy lifestyle, and visiting the families every month to give questionnaires. The measurements of children’s BMI was conducted by use WHO’s Antrho Plus software, 2007. The data were analyzed by using univariate, bivariate with Independent t-test, Mann-Whitney test and Paired t-test.Result: The results showed that there were differences in mean changes before and after the intervention, namely knowledge of the family with p=0:00 and cultural family with p=0:00.Discussion: It was concluded that the effect of TCN, CHM, and TTM could improve the knowledge and cultural family in controlling lifestyle of overweight and obese children. The importance of health education is given to families with guide books about healthy lifestyles and the impact of child obesity.